The Relationship between Internal Audit Characteristic, Audit Committee Characteristic and Interaction between Internal Audit and Audit Committee on Internal Audit Contribution - Hasnah, Haron; Tong, Chue Qun (Malaysian Institute of Corporate Governance, 2016)
The Malaysian Code of Corporate Governance (MCCG) was first introduced in 2000 and it was then revised in 2007 and 2012. This was then followed by the Bursa Malaysia Revamped Listing Requirement in 2001 and Guidelines on Internal Audit Function for Public Listed Companies in 2002. These enacted reforms aim to promote and improve corporate governance in public listed companies in Malaysia.